Development of website-based BOGA SERI media to improve understanding safety riding principles - Ratu Suci Sholikhah Wati; Didik Sukriono; Sri Untari (Himpunan Pengembang Kurikulum Indonesia, 2025)
The high number of traffic accidents that occur among teenagers, especially high school students, provides the background for the need to develop learning media that can improve their understanding of safety riding principles. Media development in the field of education is necessary because efforts to socialize these principles are considered ineffective, as evidenced by the high number of accidents in the regions. This study aims to produce and test the effectiveness of website-based BOGA SERI media in an effort to improve the understanding of these principles among grade X students of SMA Negeri 2 Tuban. The method used is research and development (RnD) with the ADDIE model. Data were collected through questionnaires, documentation, observation, and tests, and then analyzed using a parametric paired sample t-test. The results of statistical tests indicate that the website-based BOGA SERI media has a high level of validity and attractiveness, is easy to use for teachers, and is effective in enhancing students' understanding of safety riding principles. In conclusion, this media meets the criteria for feasibility and effectiveness and can be implemented as a learning medium to support efforts to maintain safety riding among students. Abstrak Tingginya angka kecelakaan lalu lintas yang terjadi pada remaja, khususnya murid SMA menjadi latar belakang perlunya pengembangan media pembelajaran yang mampu meningkatkan pemahaman prinsip safety riding. Pengembangan media dalam bidang pendidikan diperlukan karena upaya sosialisasi tentang prinsip tersebut dirasa kurang efektif, hal itu terbukti dari tingginya angka kecelakaan didaerah-daerah. Penelitian ini bertujuan menghasilkan dan menguji efektivitas media BOGA SERI berbasis website dalam upaya meningkatkan pemahaman prinsip tersebut pada murid kelas X SMA Negeri 2 Tuban. Metode yang digunakan adalah research and development (RnD) dengan model ADDIE. Data diperoleh melalui angket, dokumentasi, observasi, dan tes, kemudian data dianalisis menggunakan uji beda parametrik paired sample t-test. Hasil uji statistik menunjukkan bahwa media BOGA SERI berbasis website memiliki tingkat kevalidan dan kemenarikan yang sangat tinggi, mudah digunakan oleh guru, serta efektif dalam meningkatkan pemahaman murid mengenai prinsip safety riding. Kesimpulannya, media ini memenuhi kriteria kelayakan dan keefektifan serta dapat diimplementasikan sebagai media pembelajaran untuk mendukung upaya menjaga keselamatan berkendara pada kalangan pelajar. Kata Kunci: BOGA SERI; media pembelajaran; prinsip safety riding; website